Women’s Reasons for Attrition from a Nurse Home Visiting Program - Holland, Margaret L. (J Obstet Gynecol Neonatal Nurs, 2013)
OBJECTIVE: To describe mothers’ reasons for leaving a home visiting program early. DESIGN: Qualitative descriptive study using semi-structured interviews of mothers who dropped out of the Nurse-Family Partnership (NFP) and two focus groups with nurses and nurse supervisors at an NFP site. SETTING: A New York State site of a NFP home visitation program for low-income new mothers designed to improve the physical and emotional care of children. PARTICIPANTS: Participants included 21 mothers, 8 nurses, and 3 nurse-supervisors METHODS: Semi-structured interviews and focus groups were used to collect data, which were analyzed using content analysis. RESULTS: The program was not perceived to fit a mother’s needs when she was overwhelmed with other responsibilities, the nurse did not meet her expectations, the content was not of interest, or the mother did not desire visits after the infant was born. Nurses and mothers described need for mothers to have organizational and communication skills, such as keeping track of appointments, calling to reschedule, articulating needs, and asking for assistance. Disruptive external influences included nurse turnover and unstable living situations, including frequent moves and crowded housing. Each of these types of barriers had potential to interact with the others, creating complex combinations of challenges to retention. CONCLUSION: NFP retention might be improved by reframing program relevance to individual mothers and increasing maternal organizational and communication skill development.